Hydro-responsive wound dressings for treating hard-to-heal wounds: a narrative review of the clinical evidence—part 2. (2nd April 2022) - Rippon, Mark G; Forster, Jan; Rogers, Alan A
Abstract : This narrative clinical review summarises the key evidence in support for the use of a hydro-responsive wound dressing, HydroTac (HRWD-2, PAUL HARTMANN AG, Germany) to address key aspects associated with the treatment of both acute and hard-to-heal wounds. This review demonstrates how HRWD-2 can be used in general to address the challenges presented by a wide range of wound types and skin injuries. It highlights the ability of HRWD-2 to regulate an optimal moist wound environment that promotes wound progression and healing. Key aspects covered in this review include the dressing's ability to: promote certain phases of the wound healing response (for example, re-epithelialisation) address the concepts and needs for wound progression as set out in the TIME wound management framework provide an optimal hydration level reduce tissue trauma and pain at dressing change.